Substrate Activation of Brewers' Yeast Pyruvate Decarboxylase Is Abolished by Mutation of Cysteine 221 to Serine - Baburina, Irina; Gao, Yuhong; Hu, Zhixiang; Jordan, Frank; Hohmann, Stefan; Furey, William (Biochemistry (Easton), 1994)
Brewers' yeast pyruvate decarboxylase (EC 4.1.1.1), a thiamin diphosphate and Mg(II)-dependent enzyme, isolated from Saccharomyces cerevisiae possesses four cysteines/subunit at positions 69, 152, 221, and 222. Earlier studies conducted on a variant of the enzyme with a single Cys at position 221 (derived from a gene that was the product of spontaneous fusion) showed that this enzyme is still subject to substrate activation [Zeng, X., Farrenkopf, B., Hohmann, S., Jordan, F., Dyda, F., and Furey, W. (1993) Biochemistry 32, 2704-2709], indicating that if Cys was responsible for this activation, it had to be C221. To further test the hypothesis, the C221S and C222S single and the C221S-C222S double mutants were constructed. It is clearly shown that the mutation at C221, but not at C222, leads to abolished substrate activation according to a number of kinetic criteria, both steady state and pre steady state. On the basis of the three-dimensional structure of the enzyme [Dyda, F., Furey, W., Swaminathan, S., Sax, M., Farrenkopf, B., Jordan, F. (1993) Biochemistry 32, 6165-6170], it is obvious that while C221 is located on the beta domain, whereas thiamin diphosphate is wedged at the interface of the alpha and gamma domains, addition of pyruvate or pyruvamide as a hemiketal adduct to the sulfur of C221 can easily bridge the gap between the beta and alpha domains. In fact, residues in one or both domains must be dislocated by this adduct formation. It is very likely that regulation as expressed in substrate activation is transmitted via this direct contact made between the two domains in the presence of the activator. One can, in addition, also speculate that covalent attachment of large molecules to C221 will result in larger distortions, which will lead to greatly diminished activity, as is seen with conjugated substrate analogs, such as XC6H4CH==CHCOCOOH, explored by the authors